Pengaruh Inflasi Dan Pengangguran Terhadap Tingkat Kemiskinan Di Provinsi Jawa Timur Tahun 2005-2014 - Erina Aprillia; Icha Armanda; Selvia Apriliana; Misfi Laili Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study investigates the influence of inflation and unemployment on poverty levels in several provinces in East Java. The aim of this research is to find out how variables such as inflation and unemployment rates impact poverty levels. This research was conducted using descriptive quantitative methods. Secondary data was collected from the Indonesian Central Statistics Agency (BPS) and other parties involved in this research. Multiple linear regression analysis was carried out using the SPSS 26.0 program. The percentage of poverty level is the dependent variable, and the percentage of inflation and unemployment levels are the independent variables. The research results show that the independent variable and dependent variable simultaneously have a significant influence. Each independent variable has a different impact on the influence individually (partially). Inflation does not have a significant impact on poverty, but unemployment has a significant impact on poverty.